CONCEPT OF CONTROLLED DYNAMIC SATURATION FOR MODELING MULTIFREQUENCY STEADY STATE MODES OF MICROELECTRONIC COMPONENTS, STRUCTURES AND DEVICES - Gulin, S. P.; Gulin, A. S.; Dmitrenko, V. P.; Piza, D. M. (Radio Electronics, Computer Science, Control, 2011)
Анотація